Le parole perdute. La lingua della pedagogia tra potere, disinformazione e necessità di cambiamento - Mario Caligiuri (Studi sulla Formazione, 2022)
The rapid social transformations make even the words used to describe reality outdated. Because of its responsibilities in the social system, pedagogy before other sceinces should question itself about what is happening. Given the national educational results especially in Southern Italy, the educational institutions rather than being a solution. The essay, proposes to start again from the knowledge of words on the part of school and university teachers. This could be the indispensable renewal of the pedagogical sector that uses outdated cultural categories and words, within a university system identified as one of the national symbols of the absence of merit. Therefore, it concludes with a call for parliaments to deal with education first and the economy second. Therefore, it concludes with an invitation to Parliaments to deal firstwith education and then with economy.